2018
DOI: 10.1002/jcp.27501
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone stimulates inflammation and impairs ovarian functions of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common causes of infertility in child-bearing age women. It is characterized by ovulation dysfunction, polycystic ovaries, and hyperandrogenism. Inflammation is likely to be a crucial contributor to the pathogenesis of PCOS. However, the association between the inflammatory cytokines and the development of PCOS has not been reported. To explore the relationship between the inflammatory cytokines and PCOS, alterations of serum proteins in dehydroepiandrosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 42 publications
0
41
0
2
Order By: Relevance
“…6 g). Several inflammatory regulators, such as IL-10, IFN-γ, and TIMP-2, have been found to be lower in PCOS patients compared with healthy women [ 42 , 60 62 ]. We tested mouse serum using an antibody-based membrane assay and found that these cytokines were significantly lower in the untreated PCOS group (IL-10: 0.50 ± 0.08 fold, INF-γ: 0.79 ± 0.05 fold, TIMP-2: 0.82 ± 0.13 fold) compared with control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 g). Several inflammatory regulators, such as IL-10, IFN-γ, and TIMP-2, have been found to be lower in PCOS patients compared with healthy women [ 42 , 60 62 ]. We tested mouse serum using an antibody-based membrane assay and found that these cytokines were significantly lower in the untreated PCOS group (IL-10: 0.50 ± 0.08 fold, INF-γ: 0.79 ± 0.05 fold, TIMP-2: 0.82 ± 0.13 fold) compared with control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The published studies reported that both TIMP-2 and IFN-gamma are decreased in PCOS patients [ 60 , 61 ]. Our serum analysis in our mouse model also confirmed that these two immunomodulatory factors were decreased in PCOS mice and successfully reversed after MSC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DHEA when induced in rat models stimulates inflammation and oxidative stress causing large follicular cysts to develop in ovaries. This finding mimics human PCOS including added effects of glucose intolerance and androgen excess [ 13 ].…”
Section: Introductionmentioning
confidence: 82%
“…Ovary acts as the main androgen supplier in women, and is also an androgen-sensitive tissue [ 34 ]. Studies have indicated that androgen excess in vivo and in vitro induces a proinflammatory response in PCOS women [ 35 , 36 ]. In our study, the univariable association analysis and multivariable regression analysis revealed remarkable positive associations between follicular PTX3 level and ovarian androstenedione concentration.…”
Section: Discussionmentioning
confidence: 99%